Low Socioeconomic Status is an Independent Risk Factor for Survival After Abdominal Aortic Aneurysm Repair and Open Surgery for Peripheral Artery Disease. Issue 5 (November 2015) - Ultee, K.H.J.; Bastos Gonçalves, F.; Hoeks, S.E.; Rouwet, E.V.; Boersma, E.; Stolker, R.J.; Verhagen, H.J.M.
Abstract : Objective/Background: The association between socioeconomic status (SES), presentation, and outcome after vascular surgery is largely unknown. This study aimed to determine the influence of SES on post-operative survival and severity of disease at presentation among vascular surgery patients in the Dutch setting of equal access to and provision of care. Methods: Patients undergoing surgical treatment for peripheral artery disease (PAD), abdominal aortic aneurysm (AAA), or carotid artery stenosis between January 2003 and December 2011 were retrospectively included. The association between SES, quantified by household income, disease severity at presentation, and survival was studied using logistic and Cox regression analysis adjusted for demographics, and medical and behavioral risk factors. Results: A total of 1, 178 patients were included. Low income was associated with worse post-operative survival in the PAD cohort ( n  = 324, hazard ratio 1.05, 95% confidence interval [CI] 1.00–1.10, per 5, 000 Euro decrease) and the AAA cohort ( n  = 440, quadratic relation, p  = .01). AAA patients in the lowest income quartile were more likely to present with a ruptured aneurysm (odds ratio [OR] 2.12, 95% CI 1.08–4.17). Lowest income quartile PAD patients presented more frequently with symptoms of critical limb ischemia, although no significant association could be established (OR 2.02, 95% CI 0.96–4.26). Conclusions: The increased health hazards observed in this study are caused by patient related factors rather than differences in medical care, considering the equality of care provided by the study setting. Although the exact mechanism driving the association between SES and worse outcome remains elusive, consideration of SES as a risk factor in pre-operative decision making and focus on treatment of known SES related behavioral and psychosocial risk factors may improve the outcome of patients with vascular disease.